DIGITAL TRANSFORMATION, FIRM PRODUCTIVITY AND POLICY COORDINATION IN VIETNAM: A BUSINESS AND ECONOMICS PERSPECTIVE - Giang Thi Nguyen (PEOPLE: International Journal of Social Sciences, 2026)
Digital transformation is widely regarded as a pathway to higher firm productivity in developing economies, yet its effects remain uneven across firms. Focusing on Vietnam, this paper examines how digital transformation affects firm productivity, why outcomes differ, and what policy conditions are needed to strengthen productivity gains. The study uses a qualitative, evidence-based approach based on literature review and policy analysis. Drawing on the resource-based view, dynamic capabilities, and institutional economics, it develops an analytical framework linking business drivers, transformation mechanisms, firm-level constraints, and productivity outcomes. The analysis shows that digital transformation can improve productivity through greater operational efficiency, stronger innovation capacity, wider market access, and higher adaptive flexibility. However, these gains are limited by weak absorptive capacity, financial barriers, digital skill shortages, and fragmented policy support, especially among SMEs. The paper makes three contributions. First, it repositions digital transformation as a productivity problem rather than a technology adoption issue alone. Second, it offers a conditional framework showing that productivity gains depend on the interaction between firm capabilities and institutional coordination. Third, it identifies the policy-practice gap as a central explanation for uneven outcomes in Vietnam. On that basis, the paper proposes six policy implications for productivity-oriented digital transformation in Vietnam.